The C-reactive protein/albumin ratio as a nutritional biomarker in maintenance hemodialysis patients: a cross-sectional study of malnutrition-inflammation status assessment - Li, Mingzhu; Jiang, Zheng; Zhang, Dongmei (Frontiers in Medicine, 2025)
BackgroundThe C-reactive protein to albumin ratio (CAR) is a biomarker associated with various diseases; however, its significance in maintenance hemodialysis (MHD) patients remains unclear. This study sought to explore the relationship between the Malnutrition-Inflammation Score (MIS) and CAR in this population.MethodsIn a cross-sectional study, 231 adult MHD patients were enrolled and categorized into high (n = 98) and low (n = 133) MIS groups based on an optimala cutoff value of 7. Detailed analyses were conducted on the MIS, biochemical parameters, and other biomarker ratios to assess their relationships.ResultsSignificant differences were observed in albumin, CRP, CAR, and RAR levels (all p < 0.05). A significant association was observed between CAR and MIS with MIS (OR 1.05, p < 0.001). The area under the receiver operating characteristic curve (AUROC) for CAR in identifying nutritional and inflammatory risk was 73.85%, with an optimal cutoff value of 2.158. A non-linear relationship was also identified between MIS and CAR.ConclusionCAR is independently associated with the MIS in MHD patients and may serve as a valuable biomarker, underscoring its potential value for clinical nutritional management of this patient population.